A thermoplastic structural coating for a low-temperature composite tank lining and its coating process
By spraying the thermoplastic structural coating formed by nitrogen-containing heterocyclic thermoplastic resin on the lining of the composite storage box, the problems of liquid oxygen incompatibility and low-temperature leakage in the composite storage box are solved, and high liquid oxygen compatibility and low-temperature toughness are achieved, which is suitable for the aerospace field.
Patent Information
- Application Number
- CN202310871217.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-07-14
AI Technical Summary
The existing composite storage tanks have problems with liquid oxygen incompatibility and low temperature leakage, and the existing theories are difficult to explain experimental phenomena and cannot effectively guide the screening of material systems.
A resin matrix using nitrogen-containing heterocyclic thermoplastic resin as the coating is used to form a thermoplastic structural coating on the inner lining of the composite material storage box through the spraying process to improve liquid oxygen compatibility and low-temperature toughness.
It has achieved high liquid oxygen compatibility and toughness at low temperatures of -183℃, solved the problems of liquid oxygen incompatibility and low temperature leakage in composite storage tanks, and is suitable for aerospace.
Smart Images

Figure CN116987431B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a thermoplastic structural coating of a low-temperature composite material tank lining and a coating process thereof. Background Art
[0002] The development and progress of space technology has placed higher and higher requirements on the performance of launch vehicles, but my country's current launch vehicle technology cannot meet the needs of space missions due to its low payload. Using composite tanks instead of alloy tanks is an excellent way to reduce and increase the payload of rockets, but composite tanks still have problems with liquid oxygen incompatibility and low-temperature leakage. Studies have found that the liquid oxygen compatibility of composite materials is greatly affected by the molding process and the internal and external structure of the material. Systems with good flame retardant properties do not always meet the liquid oxygen compatibility. There is a mutual constraint between the liquid oxygen compatibility and low-temperature toughness modification of composite materials. Existing theories at home and abroad cannot explain the experimental phenomena and cannot effectively guide the screening of material systems. Therefore, in view of the difficulty in improving the intrinsic performance of low-temperature composite tanks, using toughness coatings to improve the liquid oxygen compatibility of low-temperature composite tanks is one of the effective means.
[0003] The core of ultra-low temperature resistant structural coating is the liquid oxygen compatibility of the coating matrix resin. The existing resin matrix that can be used for liquid oxygen tanks is mainly thermosetting resin matrix. Due to the confidentiality regulations of liquid oxygen tank research, there are few public data on the research of organic resin liquid oxygen compatibility. Some studies report that benzoxazine resin system, cyanate resin system, and epoxy resin system are conventional coating resin matrices. Although these resins can improve their liquid oxygen compatibility by improving flame retardancy, their low temperature toughness is limited.
[0004] The present invention adopts a nitrogen-containing heterocyclic thermoplastic resin with better low-temperature toughness and higher flame retardancy as the resin matrix of the liquid oxygen tank coating, wherein the nitrogen-containing heterocyclic thermoplastic resin has excellent flame retardancy and liquid oxygen compatibility, and can be dissolved in certain organic solvents, can be used to make coatings, and has excellent low-temperature toughness. The ultra-low temperature resistant coating developed by the resin is applied to the low-temperature composite tank, which can take into account the low-temperature toughness of -183°C and liquid oxygen compatibility. This coating has not been reported. At the same time, the size of the low-temperature composite tank is relatively large. The present invention discloses a spraying technology for a low-temperature composite tank with a diameter greater than 3111mm. Summary of the invention
[0005] In view of the problems of liquid oxygen incompatibility and low-temperature leakage in the current composite tank, a thermoplastic structural coating is applied to the inner lining to solve the problem, and a thermoplastic structural coating for the inner lining of a low-temperature composite tank and a coating process thereof are provided. The technical scheme of the present invention is as follows: in the first step, the inner surface of the composite tank is subjected to sandblasting to achieve a roughness that is conducive to the adhesion of the coating; in the second step, the polymer powder is sprayed onto the surface of the substrate in accordance with a specific spraying process by supersonic polymer powder thermal spraying to form a polymer coating; in the third step, the coating is subjected to appropriate post-treatment to complete the preparation of the coating.
[0006] In order to achieve the above object, the present invention specifically adopts the following technical scheme:
[0007] The present invention provides a thermoplastic structural coating for a low-temperature composite material tank liner. The thermoplastic structural coating for a low-temperature composite material tank liner is obtained by spraying a coating comprising the following mass fraction components:
[0008] Thermoplastic resin matrix 11%-25%;
[0009] Organic mixed solvent 91%-75%.
[0010] As an embodiment of the present invention, the thermoplastic resin matrix is a polyfluoro polyarylether resin containing a phthalazinone structure; the phthalazinone structure improves the flame retardancy of the resin, and its twisted non-coplanar structure improves the mechanical properties and ensures the solubility of the resin. Conventional polyfluoro polyarylethers are lacking in performance, and the solubility of polyarylether resins is poor. Preferably, the polyfluoro polyarylether resin has the following molecular structure:
[0011]
[0012] n is a natural number between 25 and 41.
[0013] As an embodiment of the present invention, the preparation method of the polyfluoropolyarylether resin containing diazinone structure is as follows: 1.2 mol Br-DHPZ (4-(4-hydroxyphenyl)-2,3-(3-bromo) diazinone-1-one), 1.24 mol K 2 CO 3Mix with 411-611mL toluene, start heating after nitrogen is passed, react at 111-131°C with toluene for 1-4h, cool to 91-111°C after water is removed, and proceed to the next step of reaction, add 1.21mol DFBP (perfluorobiphenyl) () and 241mL N, N-dimethylacetamide (DMAc), and finally precipitate the polymer diluted with DMAC into hot water with hydrochloric acid to obtain the target polymer Br-PPEfB (polyfluoropolyarylether containing diazinone structure). During the reaction, when the viscosity increases, add appropriate amount of solvent until the viscosity no longer increases.
[0014] As an embodiment of the present invention, the organic mixed solvent is a compound of a high boiling point solvent and a low boiling point solvent, the purpose of which is to more efficiently remove the solvent after the coating is sprayed while ensuring the solubility of the solvent in the resin matrix. The high boiling point solvent with a boiling point higher than 111°C includes one or more of cyclohexanone and N,N-dimethylformamide, and the low boiling point solvent with a boiling point lower than 111°C includes one or more of acetone, methanol, ethanol, and ethyl acetate. The volume ratio of the high boiling point solvent to the low boiling point solvent is 1:3 to 3:1, preferably 1:1.
[0015] As one embodiment of the present invention, the thickness of the thermoplastic structural coating is 31-111 microns.
[0016] The present invention also provides a method for preparing the thermoplastic structural coating, comprising the following steps:
[0017] S1, dissolving a thermoplastic resin matrix in a high boiling point solvent, and then adding a low boiling point solvent to obtain a coating;
[0018] S2. Spray the prepared coating onto the inner lining of the low-temperature composite material storage tank, and dry it to obtain a thermoplastic structural coating.
[0019] As an embodiment of the present invention, in step S1, the obtained coating is further subjected to a bubbling treatment, specifically, the bubbling of the system is carried out by ultrasound and vacuum.
[0020] As an embodiment of the present invention, in step S2, the spraying pressure is 1.1-1.5 MPa, the spray gun is 15-25 cm away from the low-temperature composite material tank lining, the spraying times are 2-4 times, and drying is performed after each spraying.
[0021] As an embodiment of the present invention, in step S2, the drying process is: drying at 41°C to 81°C for 1.5-1.5h, and drying at 121°C to 181°C for 1.5-1h. Low-temperature drying below 111°C is to achieve the effect of surface drying of the coating and avoid problems such as coating deformation that may be caused by direct high-temperature drying. High-temperature drying is to completely remove the solvent in the coating. Drying is carried out by hot air, which is blown in from the upper manhole cover of the low-temperature composite material storage tank and naturally released from the lower manhole cover of the low-temperature composite material storage tank.
[0022] As an embodiment of the present invention, in step S2, the paint is sprayed and the roughness of the lining surface is improved by sandblasting, and the roughness is 2.4≤Ra≤3.6.
[0023] The high boiling point solvent is added first to fully dissolve the resin matrix, and the low boiling point solvent is added later to reduce the overall azeotropic point and facilitate subsequent solvent treatment. The correct coating configuration steps can effectively avoid the difficulty of post-processing. Different spraying processes will affect the uniformity and thickness of the prepared coating, and the drying process will affect the final forming of the coating.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The low-temperature composite tank lining thermoplastic structural coating of the present invention uses polyfluoropolyarylether with excellent performance as filler, which is dissolved in an organic solvent by magnetic stirring to prepare a coating, and the coating is prepared by a specific spraying process to obtain the required liquid oxygen compatible coating. The coating has high mechanical properties, high temperature resistance (low temperature resistance and certain high temperature resistance (-183°C to 121°C), and excellent liquid oxygen compatibility, and can be used in the aerospace field.
[0026] (2) The preparation process of the present invention is universal and can be widely used in the preparation of lining coatings of large devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0028] Figure 1 It is a structural diagram of a low-temperature composite material storage tank; 1-upper manhole cover, 2-lower manhole cover, 3-inner shell section, 4-outer cylinder section. DETAILED DESCRIPTION
[0029] The low-temperature composite material tank liner thermoplastic structural coating and its coating process of the present invention are described below in conjunction with the accompanying drawings and embodiments. It should be understood that these embodiments are only used to explain the present invention and are not used to limit the scope of the present invention. It should be understood that after reading the content of the present invention, those skilled in the art will make various changes and modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
[0030] The test standards of the present invention are as follows:
[0031] (1) Coating flexibility test
[0032] According to GB / T 1731-2121, after the coating is cured, use both hands to press the test plate tightly against the shaft of the specified diameter of the paint film flexibility tester, and use the two thumbs to bend the test plate around the shaft at a steady speed within 2 to 3 seconds. After bending, the two thumbs should be symmetrical to the center line of the shaft. Observe whether the paint film has mesh, cracks and peeling. Flexibility 1mm means: after testing on a shaft with a shaft diameter of 1mm, the coating has no obvious changes.
[0033] (2) Coating impact strength test
[0034] According to GB / T 1732-2121, place the impact tester on a stable platform, and the guide tube should be perpendicular to the horizontal plane. Use the weight controller to adjust the weight of the impact tester to a certain height, and place the test plate flat on the base with the paint film facing up (forward impact) or facing down (recoil impact). The distance between the edge of the test plate at the impact point and the edge of the test plate shall not be less than 11mm, and the distance between the edges of adjacent impact points shall not be less than 11mm. Press the weight controller button, and the weight will fall freely on the punch. Take out the test plate and observe whether the paint film on the test plate has cracks, wrinkles and peeling. Impact strength of 51cm means: after the test plate is impacted by a 51cm high weight, there is no obvious change on the coating surface.
[0035] (3) Liquid oxygen shock sensitivity test
[0036] According to the standard "Test Method for Mechanical Shock Sensitivity of Materials in Liquid Oxygen and Pressurized Oxygen Environments" (QJ3177-2113), the mechanical impact test of the samples in liquid oxygen environment was carried out in batches (21 pieces per batch), and the test results were observed and recorded.
[0037] (4) Temperature resistance cycle test
[0038] The coated sample was immersed in liquid nitrogen for 1.5 hours, taken out, and placed in a forced air oven at 121°C for 1.5 hours. This was counted as one cycle, and whether the coating was broken or fell off was recorded.
[0039] The polyfluoropolyarylether resin containing a phthalazinone structure used in the examples and comparative examples is prepared by using the existing technology, and the steps are as follows:
[0040] In a 1111mL three-necked flask equipped with a mechanical stirrer, a water separator, a condenser, and a nitrogen inlet, 1.2 mol Br-DHPZ, 1.24 mol K 2 CO 3 and 511mL toluene, and then heated after nitrogen was passed. The reaction was carried out at 121°C using toluene to carry out water for 3h. After the water was carried out, the temperature was lowered to 111°C for the next step of reaction, and 1.21mol DFBP and 241mL N, N-dimethylacetamide (DMAc) were added. During the reaction, when the viscosity increased, the solvent was appropriately added until the viscosity no longer increased. Finally, the polymer diluted with DMAC was precipitated into hot water with a small amount of hydrochloric acid to obtain the target polymer Br-PPEfB as shown below.
[0041]
[0042] By calculating the molecular weight of the product, the n value is about 31 (the molecular weight is 18k, the molecular weight of the structural unit is 611, then the n value is about 31). The molecular weight of the product can be controlled within a certain range by adding the proportion of the reactants to ensure that the n value of the product is within the required range.
[0043] Example 1
[0044] This embodiment prepares a low-temperature composite material tank lining thermoplastic structural coating, the steps are:
[0045] 4 g of polyfluoropolyarylether resin containing diazinone structure was fully dissolved in 13 g of cyclohexanone solvent at room temperature, and possible impurities were filtered out. Then 13 g of acetone was slowly added, and the system was bubbled by ultrasound and vacuum pumping. The coating was prepared.
[0046] The low temperature composite material tank structure used is as follows Figure 1 As shown, an upper manhole cover 1 is provided at the bottom of the tank, a lower manhole cover 2 is provided at the bottom, the inside of the tank is an inner shell section 3, and the outside is an outer cylinder section 4. The roughness of the lining surface is improved by sandblasting (Ra 2.4).
[0047] The prepared coating was sprayed at a spray pressure of 1.2MPa, with the spray gun 21cm away from the inner lining of the low-temperature composite material tank. Spraying was performed 4 times, and the drying process for each time was as follows: 61℃ hot air was blown in from the upper manhole cover of the low-temperature composite material tank, and after drying for 1h, the hot air was raised to 151℃ and dried for 1h. The hot air was naturally released from the lower manhole cover of the low-temperature composite material tank.
[0048] The thickness of the obtained coating is 45 microns, the coating impact strength is 51cm (drop hammer impact); the flexibility is 1mm, the temperature resistance cycle is more than 111 times, and the coating liquid oxygen impact sensitivity coefficient is 1%. The table shows the experimental results tested in accordance with the provisions of the standard "Experimental Method for the Sensitivity of Materials to Mechanical Shock in Liquid Oxygen and Pressurized Oxygen Environments" (QJ3177-2113). The liquid oxygen impact sensitivity coefficient is calculated based on the experimental results according to the formula shown in Formula 1:
[0049]
[0050] In the formula, N is the number of independent repeated impact tests of the sample, n is the total number of a certain type of impact phenomenon, Ci is the impact sensitivity weighting coefficient, and the weighting coefficient is specified as follows: Sustaining combustion C1 = 1; Explosion C2 = 1.9; Spark C3 = 1.7; Spark C4 = 1.6; Charred spots C5 = 1.4. For example: Assuming that a certain material has 2 explosions, 5 sparks, and 6 charred spots in 21 impacts in the liquid oxygen shock sensitivity test, the corresponding impact reaction sensitivity coefficient is: IRS = (1*1+2*1.9+5*1.7+1*1.6+6*1.4) / 21 = 58.5%.
[0051] The test results are shown in Table 1 below:
[0052] Table 1
[0053] frequency No explosion sound No flash No scorching No noticeable fading 1 √ √ √ √ 2 √ √ √ √ 3 √ √ √ √ 4 √ √ √ √ 5 √ √ √ √ 6 √ √ √ √ 7 √ √ √ √ 8 √ √ √ √ 9 √ √ √ √ 11 √ √ √ √ 11 √ √ √ √ 12 √ √ √ √ 13 √ √ √ √ 14 √ √ √ √ 15 √ √ √ √ 16 √ √ √ √ 17 √ √ √ √ 18 √ √ √ √ 19 √ √ √ √ 21 √ √ √ √
[0054] Experimental standard: "Test method for sensitivity of materials to mechanical shock in liquid oxygen and pressurized environment" (QJ3177-2113); impact energy: 98J; test equipment: FYDZ-3 liquid oxygen shock testing machine; test environment: temperature 11°C, humidity 48%.
[0055] Example 2
[0056] This embodiment prepares a low-temperature composite material tank lining thermoplastic structural coating, the steps are:
[0057] 4 g of polyfluoropolyarylether resin containing diazinone structure was fully dissolved in 11 g of cyclohexanone solvent at room temperature, and possible impurities were filtered out. Then 11 g of ethyl acetate was slowly added, and the system was bubbled by ultrasound and vacuum pumping. The coating was prepared.
[0058] The low temperature composite material tank structure used is as follows Figure 1As shown, an upper manhole cover 1 is provided at the bottom of the tank, a lower manhole cover 2 is provided at the bottom, the inside of the tank is an inner shell section 3, and the outside is an outer cylinder section 4. The roughness of the lining surface is improved by sandblasting (Ra 2.4).
[0059] The prepared coating was sprayed at a spray pressure of 1.5 MPa, with the spray gun 21 cm away from the inner lining of the low-temperature composite material tank. Spraying was performed twice, and the drying process each time was as follows: 61°C hot air was blown in from the upper manhole cover 1 of the low-temperature composite material tank, and after drying for 1 hour, the hot air was raised to 151°C and dried for 1 hour. The hot air was naturally released from the lower manhole cover 2 of the low-temperature composite material tank.
[0060] The thickness of the obtained coating is 85 microns, the impact strength of the coating is 51 cm (drop hammer impact), the flexibility is 1 mm, and the liquid oxygen impact sensitivity coefficient of the coating is 1%.
[0061] Comparative Example 1
[0062] In this comparative example, a low-temperature composite tank lining thermoplastic structural coating was prepared, and the steps were basically the same as those in Example 1, except that the thermoplastic resin matrix did not contain a phthalazinone structure, and a polyfluoropolyarylether resin of biphenyl diphenol was used instead. The obtained coating had poor performance, no phthalazinone structure, and the coating flexibility was greater than 11 mm and the impact strength was less than 21 cm.
[0063] Comparative Example 2
[0064] In this comparative example, a low-temperature composite material tank lining thermoplastic structural coating was prepared, and the steps were basically the same as those in Example 1, except that the thermoplastic resin matrix was 2,6-difluorobenzonitrile and 4,4'-difluorodiphenyl sulfone. The obtained coating had poor performance, no phthalazinone structure, and the coating flexibility was greater than 5 mm and the impact strength was less than 31 cm.
[0065] Comparative Example 3
[0066] In this comparative example, a low-temperature composite material tank lining thermoplastic structural coating was prepared, and the steps were basically the same as those in Example 1, except that the solvent was 26g of cyclohexanone solvent. The obtained coating had poor performance, only using a high boiling point solvent, the solvent was not easy to remove after spraying, the coating surface had obvious concave-convex morphology, and the impact strength was less than 41cm.
[0067] Comparative Example 4
[0068] In this comparative example, a low-temperature composite material tank lining thermoplastic structural coating was prepared, and the steps were basically the same as those in Example 1, except that the solvent was 26g of acetone. The obtained coating had poor performance, and only a low-boiling point solvent was used, the resin matrix was not fully dissolved, there were obvious protrusions on the coating surface, and the coating flexibility was greater than 11mm.
[0069] Comparative Example 5
[0070] In this comparative example, a low-temperature composite tank lining thermoplastic structural coating was prepared, and the steps were basically the same as those in Example 1, except that the coating was sprayed 8 times. The obtained coating had poor performance, with a coating thickness greater than 61 microns and a flexibility greater than 5 mm.
[0071] Comparative Example 6
[0072] In this comparative example, a low-temperature composite material tank lining thermoplastic structural coating was prepared, and the steps were basically the same as those in Example 1, except that the drying step was only dried at 121°C for 3 hours. The obtained coating had poor performance, and the one-step drying affected the coating formation. The coating shrank significantly, the coating thickness was greater than 61 microns, and the flexibility was greater than 11 mm.
[0073] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A thermoplastic structural coating for a low-temperature composite tank lining, characterized in that: The low-temperature composite material tank lining thermoplastic structural coating is obtained by spraying a coating comprising the following mass fraction components: Thermoplastic resin matrix 10%-25%; Organic mixed solvent 90%-75%; The thermoplastic resin matrix is a polyfluoropolyarylether resin containing a phthalazinone structure; The molecular structure of the polyfluoropolyarylether resin containing a phthalazinone structure is as follows: n is a natural number between 25 and 40; The organic mixed solvent is a composite combination of a high boiling point solvent having a boiling point higher than 100°C and a low boiling point solvent having a boiling point lower than 100°C; The high boiling point solvent includes one or more of cyclohexanone and N,N-dimethylformamide; the low boiling point solvent includes one or more of acetone, methanol, ethanol and ethyl acetate.
2. The thermoplastic structural coating according to claim 1, characterized in that The volume ratio of the high boiling point solvent to the low boiling point solvent is 1:3 to 3:
1.
3. A method for preparing a thermoplastic structural coating according to claim 1, characterized in that: The steps include: S1, dissolving a thermoplastic resin matrix in a high boiling point solvent, and then adding a low boiling point solvent after the dissolution to obtain a coating; S2, spraying the prepared coating on the inner lining of the low-temperature composite material storage tank, and drying to obtain a thermoplastic structural coating; In step S2, the spraying times are 2-4 times, and drying is performed after each spraying; the drying process is: drying at 40°C-80°C for 0.5-1.5h, and drying at 120°C-180°C for 0.5-1h.
4. The preparation method according to claim 3, characterized in that: In step S1, the obtained coating is further subjected to a bubbling treatment, specifically, the coating is bubbling by ultrasound and vacuum.
5. The preparation method according to claim 3, characterized in that: In step S2, the spraying pressure is 0.1-0.5 MPa, and the distance between the spray gun and the inner lining of the low-temperature composite material tank is 15-25 cm.
Citation Information
Patent Citations
Polyarylether containing triaryl s-triazine ring and phthalazone diphenyl structure and preparation method thereof
CN101591431A